Like climbing Jacob's ladder: An art-based exploration of the comprehensive exam process. (April 2015) - Shields, Sara Scott
The comprehensive exam process is a rite of passage in the scholarly world, and as such the movements of this process often feel like a guarded secret to graduate students. As a PhD candidate, I left the comprehensive exam process feeling both initiated and inundated. This article is an attempt to uncover the secret that is the comprehensive exam process, but more importantly this article is an artful documentation of my journey through the process. Through arts-based engagement with artifacts from my comprehensive exam process I hope to explore and uncover the power this academic journey holds so other graduate students can enter their journey with open eyes.